MODEL INVESTIGASI KELOMPOK UNTUK MENINGKATKAN KEMAMPUAN PROFESIONAL CALON GURU DALAM PROSES PEMBELAJARAN NILAI-NILAI MORAL PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN: Studi Terhadap Kemampuan Mahasiswa Sebagai Calon Guru PPKn di STKIP PGRI Pontianak. - Aunurrahman, - (2004)
This research was substantially intended to determine and develop a group investigation model relevant and applicable with the efforts of improving teachers' professional skills in the learning process of moral and citizenship education (PPKn). This model was developed through Educa-tional Profession subject to students of PPKn at STKIP PGRI Pontianak. Through the combination of qualitative and quantitative approaches, this research found several findings as follow: (1) the group investigation model was obviously able to improve the students' knowledge and insight to the learning process of PPKn moral values, improve the students' res-ponsibility, build better relationship and appreciation to the other people and improve their insight to the group investigation as one of the learning models; (2) in order to improve the effectiveness of the model development results, therefore, the stages of the model development mechanism and procedures should be integratedly carried out starting from determining and formulating the stages of the conceptual model to the try out of the model; (3) an intensive coordination between lecturers, students and schools, as the sites of investigation, was the basic prerequisites to realize the effectiveness of the model being developed; (4) the data were collected through observation, interview and direct dialog with students; (5) the efforts in developing the professional skills of PPKn teachers at schools was not directed to build the essential aspects of learning and the moral values of the students in specific ways; (6) the efforts of improving the skills of students as prospective teachers, STKIP PGRI Pontianak continuously executed several steps in improving the quality of teachers and curriculum development. However, the empowerment of the students' associations was not optimal and the efforts of reforming the ways of lecturing were not optimal yet since most of the lecturers were still applying conventional approaches in their lectures. In accordance with the above findings, it is recommended that: (1) the model could be widely developed in various subjects in order to improve the knowledge and experiences of the students; (2) the development of the model should be initiated by discussions and adequate knowledge enrich-ment to the students especially in the mechanism of data gathering and analysis of research findings; (3) STKIP as an institution providing pros-pective educators (LPTK) should be able to explore in concrete ways about the profiles of the graduates who were expected-through developing progressive and innovative steps-to realize the roles of the institution to be more optimal; (4) in spite of its various limitations, the research contributed many inspirations for further research to deepen or widen the findings of this research.